Maladaptive learning and memory in hybrids as a reproductive isolating barrier - Rice, Amber M.; McQuillan, Michael A. (Proceedings of the Royal Society. B, Biological sciences, 2018)
Selection against hybrid offspring, or postzygotic reproductive isolation, maintains species boundaries in the face of gene flow from hybridization. In this review, we propose that maladaptive learning and memory in hybrids is an important, but overlooked form of postzygotic reproductive isolation. Although a role for learning in premating isolation has been supported, whether learning deficiencies can contribute to postzygotic isolation has rarely been tested. We argue that the novel genetic combinations created by hybridization have the potential to impact learning and memory abilities through multiple possible mechanisms, and that any displacement from optima in these traits is likely to have fitness consequences. We review evidence supporting the potential for hybridization to affect learning and memory, and evidence of links between learning abilities and fitness. Finally, we suggest several avenues for future research. Given the importance of learning for fitness, especially in novel and unpredictable environments, maladaptive learning and memory in hybrids may be an increasingly important source of postzygotic reproductive isolation.